Evaluation the pathogenecity of campylobacterjejuni hepatic toxin - Fahim Abbas, Aalaa; Al-Thahabb, Azhar Imran (Al-Qadisiyah Journal of Pure Science, 2018)
The current study investigated the gene responsible of hepatic toxin in Campylobacter jejuniisolatesthat isolated from children suffering diarrhea using polymerase chain reaction technique (PCR). The results showed that only one C. jejuni isolate that obtained from watery diarrheal stool was carrying hepatic toxin gene. Hepatic toxin was extracted fromproducedC.jejuniisolateand tested its effectiveness by liver function test in Swiss mice female type Balb/c (Mus musculus). The intravenous injection of 100 Î¼g / 0.5 ml of hepatic toxin extract led to a significant increase in the mean concentration of liver enzymes Glutamate oxaloacetate transaminase (GOT) and Glutamate pyruvate transaminase (GPT), while the increase was not significant in mean concentration of the enzyme Alkaline phosphatase (ALP) compared with the control mice. In addition, histopathological study showed that hepatic toxinextracthad severe effects represented by multiple foci of inflammatory cells, bloody congestion, and necrosis in liver, hemorrhage and penetration of inflammatory cells in the spleen, while no histological changes was induced by hepatic toxin extract in the intestine.